Budgetary Effects of Including the CEC into Dynamic Modulation - Martin Banse; Harald Grethe (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
The EU Commission suggests to exclude CEC from the dynamic modulation mechanism, being part of the MTR package. This article looks at the distributional aspects of including the CEC into dynamic modulation. Under the current accession proposal the CEC would account for only 18% of the rural development budget by 2006. If modulation would be realised with the CEC being excluded this share would drop to 14% by 2010. According to the criteria proposed by the Commission for the distribution of the modulation budget the CEC would get a higher share of the modulation budget if they were included as they account for high shares in agricultural area and employment, and their GDP per capita is relatively low. Based on the assumptions made for this article they would be eligible for about 66% of the modulation budget. As a result of their participation in the modulation mechanism their share in the rural development budget would be at 30% by 2010. The financial net gains for the CEC from participation are estimated to be at 1.7 bln. Euro.
Keywords: 330